The Causal Map of The Mayor’s Policies on Regional Competitiveness - Prihantika, Ita; Hardjosukarto, Sudarsono (UI Scholars Hub, 2012)
This paper explores the leadership style of a direct-elected Mayor in the new era of local administration. Solo city, under the leadership of Mayor Joko Widodo, along with his political partner, Vice Mayor F.X. Hadi Rudyatmo, is currently referred to as practicing the best local government. The leadership of the political partner is perceived to be a role model of leadership style in the new era. A step by step guidance of cognitive mapping introduced by Ackerman et. al. (1992) is applied to construct the cognitive map and causal map of the Mayor’s policies on regional competitiveness. Meanwhile, the NUMBER method developed by Kim (2000 and 2005) is used to convert the causal map into a dynamic model system of the City Mayor’s policies. Many pro-people related policies and programs are believed to be important factors in enhancing regional competitiveness during the leadership of Mayor Joko Widodo. This study contributes to provide a role model of regional leaders’ best practice overview in building the area, particularly building the regional competitiveness. Keywords: regional competitiveness, leadership style, cognitive map, causal map, NUMBER method